2017
DOI: 10.1101/157453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatially dispersed synapses yield sharply-tuned place cell responses through dendritic spike initiation

Abstract: ACKNOWLEDGMENTSThe authors thank members of the cellular neurophysiology laboratory for helpful discussions and for comments on a draft of this manuscript.The literature offers evidence for a critical role of spatially-clustered iso-feature synapses in eliciting dendritic spikes essential for sharp feature selectivity, with apparently contradictory evidence demonstrating spatial dispersion of iso-feature synapses. Here, we reconcile this apparent contradiction by demonstrating that the generation of dendritic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(156 reference statements)
1
2
0
Order By: Relevance
“…Place cells within the CA1 fire specifically when a rat occupies a particular location in the environment (28). Dendritic spiking has been proposed to be essential in driving formation of place-related firing in CA1 neurons (4,29,30), and computational studies have suggested that sharp spatial tuning of place cell responses is supported by dendritic spikes (31). Indeed, we have found significant broadening of place representations in epileptic animals, consistent with previous studies in different models of epilepsy (19)(20)(21)32).…”
Section: Discussionsupporting
confidence: 90%
“…Place cells within the CA1 fire specifically when a rat occupies a particular location in the environment (28). Dendritic spiking has been proposed to be essential in driving formation of place-related firing in CA1 neurons (4,29,30), and computational studies have suggested that sharp spatial tuning of place cell responses is supported by dendritic spikes (31). Indeed, we have found significant broadening of place representations in epileptic animals, consistent with previous studies in different models of epilepsy (19)(20)(21)32).…”
Section: Discussionsupporting
confidence: 90%
“…In most encoding or homeostatic scenarios involving changes in constituent components, however, the functional outcome that is expected is a more quantitative readout of, say, firing rate or calcium concentration altered or returned to specific values . Therefore, a widely employed alternate interpretation (Basak & Narayanan, ; Foster et al, ; Goldman et al, ; Marder, ; Marder & Goaillard, ; Marder et al, ; Marder & Taylor, ; Migliore et al, ; Mishra & Narayanan, ; Mittal & Narayanan, ; Prinz et al, ; Rathour & Narayanan, ; Rathour & Narayanan, ; Srikanth & Narayanan, ; Taylor et al, ) is where degeneracy is assessed as the ability of different structural components to elicit quantitatively similar functional measurements. With reference to our chosen example, this would translate to assessing degeneracy as the ability to achieve a specific range of values of resonance frequency with disparate combinations of parameters (Figure b).…”
Section: Degeneracy: Foundations From the Perspective Of An Encoding mentioning
confidence: 99%
“…However, given the in vitro nature of the experiments, we cannot claim to have mimicked the exact network activity experienced by SCs during the grid field crossings or other behavioral activities. Also, differences can result from the actual spatial distribution of synapses 52 and the dendritic distribution of HCN channels in SCs, which, unfortunately, lacks the quantifying experimental data in the literature. It is possible that with spatially distributed synapses, the synaptic inputs can interact with the active dendritic conductances to shape the computations differently.…”
Section: Simulation Of the Stochastic Synaptic Activity Through The D...mentioning
confidence: 99%